Comparative analysis of allele frequencies for DNA polymorphisms associated with disease and economically important traits in the genomes of Russian and foreign cattle breeds - A. V. Igoshin; G. A. Romashov; E. N. Chernyaeva; N. P. Elatkin; N. S. Yudin; D. M. Larkin (Вавиловский журнал генетики и селекции)
The genetic makeup of a breed including its genetic differences from other breeds determines its appearance and characteristics, including economically important traits and resistance to pathologies. To date, many loci controlling significant phenotypes have been identified, which is successfully used in the world practice of marker-assisted selection to improve breed properties. The aim of this study was a comparative analysis of frequencies for known causative nucleotide substitutions, insertions and deletions associated with disease and economically important traits in Russian and foreign cattle breeds. As a result, we identified frequencies of these DNA polymorphisms in the populations of Russian cattle breeds, compared them with those of foreign populations of the same breed, as well as other foreign breeds. Our results indicate similarities in frequencies for most of such alleles within breeds (populations of Russian and foreign breeding), as well as the relationship between the causative allele prevalence and the presence of phenotypic traits under the effect. We also found an excess of some undesirable alleles in the Russian cattle populations, which should be paid attention to when designing breeding programs. We found that the alleles increasing fertility in the Hereford breed have a higher frequency in the Russian Hereford population compared to the foreign counterpart. Interestingly, unlike for the European breeds, for Asian Turano-Mongolian Wagyu and Yakut cattle, there was a less clear link between phenotypic traits and frequencies of known causative alleles. Our work points to specific genetic variants that could be used to improve and/or maintain the performance of certain cattle breeds bred in the Russian Federation.